‎Наум – објавувач на Божјата казна и пророк на Божјата утеха - Ѓоко Ѓорѓевски (ПБФ „Свети Климент Охридски“ - Скопје, 2021)
The present research aims to provide a brief introduction of the Book of Nahum, investigating the authorship, historical circumstances, time and place of the writing, as well the literary aspects of the book. The historical setting of the book of Nahum will be addressed, followed by the audience that the author intended to reach and the literary structure of the book. Finally, the most important theological topics as an application of the book for the present days and the modern believers is done.